The theory of economic underdevelopment and its applicability to the Rhodesian economy - Clarke, Duncan G, 1948- (Rhodes University, Faculty of Commerce, Department of Economics, 1969)
According to the canons of conventional economic philosophy the process of economic interpretation should be value neutral and strictly fall within the bounds of normative science. This approach is concerned not with goal setting but only with the technical possibilities of alternative means of successful tactics in a given overall strategy. It is the author's thesis that such premises patently ignore the fundamental truths of development problems, and that there exists a genuine need to bridge the gap that demarcates theory from practicality and truth from illusion. To seek "development" implies a challenge to the "status quo" of menial existence and perpetual servitude to the inhospitable forces of ones own environment. This attitude is in itself a value judgement, and in underdeveloped societies it is more than a mere academic quibble. Accordingly, this paper not only implicitly assumes "development" to be a desirable goal but also that it is necessary, and the objective of this study of an underdeveloped community shall be to examine the theoretical relevance, or otherwise, of general and partial theories of underdevelopment against the quantitative and qualitative evidence of the course of events that have in the past, and are likely in the future, to influence the development of the "Rhodesian economy".
Keywords: Zimbabwe -- Economic conditions; Economic development -- Zimbabwe; Developing countries -- Economic conditions